Risk for Imminent Delivery in Preeclampsia Based on the sFlt-1/PlGF Ratio: Do We Need New Cut-Offs? - Enengl, Sabine; Oppelt, Peter; Stelzl, Patrick; Scharnreitner, Iris; Altmann, Reinhard; Grienberger, Julia; Hermann, Philipp; Wagner, Helga; Rezk-Füreder, Marlene; Damian, Ilinca; Maghörndl, Lena (Geburtshilfe und Frauenheilkunde, 2025)
It is still difficult to predict the outcome of preeclampsia and determine the individual procedure with regards to the time of birth. Cut-offs of the sFlt-1/PlGF ratio with a high risk for imminent delivery have been previously published and analyzed by our study group, but could not be confirmed. The aim of the current study is to re-evaluate the described cut-off values again in a new period of time.We performed a retrospective analysis (IRB 1279/2020) including all preeclampsia patients delivering in our department over a 3-year period. Patients were divided into 2 groups – gestational week 24+0–33+6 with an s-Flt1/PlGF > 655.2 and 34+0–37+0 weeks with an sFlt-1/PlGF > 201 and were compared with preeclampsia patients of the same weeks with sFlt-1/PlGF values below the described cut-offs. Correlation between sFlt-1/PlGF ratio and time to delivery was assessed.The association between sFlt-1/PlGF above the threshold and delivery within 48 h is significant for the high ratio early group (p < 0.01) but not for the high ratio late group (p = 0.62). In the early group, 60% of patients with sFlt-1/PlGF > 655.2 but only 8% in the low ratio group delivered within 48 h. In both the early and the late preeclampsia group, a high number of patients remained pregnant even though they showed elevated ratios.High sFlt-1/PlGF ratios seem to correlate with a shorter pregnancy duration to some extent. Nevertheless, not all patients need to be delivered within 48 h, so the decision should never be based on the laboratory test alone.
Keywords: preeclampsia; sFlt-1/PlGF; soluble fms-like tyrosine kinase-1; placental growth factor; time to delivery